1D van der Waals Nb2Pd3Se8-Based n-Type Field-Effect Transistors Prepared by Liquid Phase Exfoliation - Choi, Kyung Hwan; Jeon, Jiho; Jeong, Byung Joo; Chae, Sudong; Oh, Seungbae; Woo, Chaeheon; Kim, Tae Yeong; Ahn, Jungyoon; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Advanced Materials Interfaces, 2022)
Recently, the 1D ternary transition metal chalcogenide Nb2Pd3Se8 has been reported as a promising channel material for the field-effect transistors (FETs) with high performance transport behavior. Its structural characteristic of weak van der Waals (vdW) forces between unit ribbons allows for the isolation of high quality Nb2Pd3Se8 nanowires from the bulk crystal that are similar to typical layered 2D materials. This study reports on the liquid phase exfoliation (LPE) of 1D vdW Nb2Pd3Se8 to predict the optimal solvent in terms of the total surface tension and polar/dispersive component ratio. Among the various test solvents, N-methyl-2-pyrrolidone and dimethylformamide are found to be the best solvents for the exfoliation and stabilization of the Nb2Pd3Se8 nanowires due to their well-matched total surface tensions and polar/dispersive component ratios. Additionally, FETs are fabricated on the LPE-processed Nb2Pd3Se8 nanowires, and the charge transport behavior is characterized at room temperature. The FETs exhibit n-type characteristics with an Ion/Ioff ratio and field-effect mobility up to ≈103 and 15 cm2 V−1 s−1. This study on the LPE of novel Nb2Pd3Se8 nanowires is an important step toward various practical applications in nanoelectronics.
Keywords: 1d van der waal material; Field-effect transistor; Liquid Phase; Liquid phase exfoliation; Liquid phasis; N-type behavior; Surface tension component; Tension components; Transport behavior; Van der Waal; 1D van der Waals materials; field-effect transistors; liquid phase exfoliation; n-type behavior; surface tension components